Preparation of decellularized meniscal scaffolds using sonication treatment for tissue engineering - Noor Azmi, Azran Azhim; Ono, T; Fukui, Y.; Morimoto, Y.; Furukawa, Katsuko; Ushida, Takashi (IEEE, 2013)
Scaffolds play a key role in the process of regeneration and morphogenesis of tissue or organ. We have developed a novel sonication decellularization system to prepare decellularized bio-scaffolds in a short treatment time. The aim of the study is to investigate sonication decellularization condition that completely decellularize meniscus can be changed as well as to maintain the biomechanical parameters of scaffolds. The meniscus samples were decellularized using sonication treatment. The treated samples were evaluated histologically by EVG for cell removal, picrosirius red for content of collagen type I and III, and safranin-O/fast green staining for content of glycosaminoglycan, and SEM for observation of scaffold surface. Indentation apparatus was used to analyze the unconfined deformation under load of native and decellularized menisci. The load parameters which are stiffness, compression and residual force were not significantly different compare with native and sonicated scaffolds. However, the content of extracellular matrix and its fiber alignment changed significantly due to sonication treatment as observed by SEM and safranin-O/fast green staining, respectively. The removal of immunogenic cell components by sonication decellularization as well as maintain its biomechanical strength of decellularized scaffolds, so that it has potential to use as an implant material for tissue engineering of menisci.